Assessing Contract Worker Loyalty in the Health Sector: An Empirical Evidence - Dyah Ayu Purwaniningtyas; Isaac Jogues Kiyok Sito Meiyanto (International Journal Labs, 2022)
This study aims to understand how the contract worker loyalty in the health sector and role of organizational climate on contract worker loyalty. The research participants consisted of 288 contract worker in the health sector Demak District Hospital. Participants consisted of 109 nursing medical personnel, 65 non-nursing medical personnel, and 114 support staff, which is divided into 109 men and 179 women. This research design uses a non-experimental quantitative approach with a non-probabability sampling method, namely purposive sampling technique. The measuring instrument used in this research are contract worker loyalty scale and organizational climate scale. The data analysis technique used is simple linear regression analysis. The results of this study indicate that the role of organizational climate on the contract worker loyalty by 25,8%. The aspect support and warmth of the organizational climate is the highest aspect that determines the contract worker loyalty by 12,85%. Therefore, organizations are expected to provide better support and warmth for contract worker loyalty.